Evaluation of Native Rooster Based on Breeding Value of trait of Macroscopic and Microscopic Semen Quality - Sutiyono Sutiyono; E. Kurnianto; Sutopo Sutopo; D. K. Ariyanto; D. Samsudewa (Jurnal Sain Peternakan Indonesia, 2021)
The aim of this research is to a determined the breeding value of native roosters based on macroscopic and microscopic semen. Ten native roosters were used in this research. Complete individual cage, semen collection tools and substance, macroscopic and microscopic tools, and substance were used in this research. The native rooster was rested for 2 weeks. Massage techniques were used for semen collection. Parameters observed were volume, pH, color, viscosity, smell, sperm concentration, and sperm livability. The semen collection was repeated 5 times. One-way analysis of variances was used for data analysis with the tools SPSS 16. The breeding value was estimated based on primary traits of semen and calculated for each rooster to make a rank. The results showed that significant parameters (P<0,05) are semen volume and sperm concentration, while the non-significant parameters (P?0,05) are pH semen and sperm livability. Semen color is yellowish-white, semen viscosity is medium-viscous and smell is spermin. The results of breeding value rank are rooster numbers 6, 7, 5, 3, 2, 4, 8, 9, 10, and 1. The conclusion is the breeding value of Native roosters is varied. The recommendation is Native chicken breeding need to apply selection used breeding value based on semen quality.